Penguatan Profil Pelajar Pancasila Dengan Pengintegrasian Nilai-Nilai Kebangsaan Melalui Pembelajaran Bahasa Indonesia di SMP Kabupaten Karanganyar - Rahma Nur Laila; Burhanuddin Al Ghiffari; Istingatus Oktavia Puji Saputri; Izi Primassa; Raheni Suhita; Kundharu Saddhono (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
National values are an important foundation in understanding and loving Indonesia as a homeland. Middle school is a crucial character-building period for students because they begin to form a deep understanding of the values that form the moral and ethical foundation in everyday life. This article aims to explore the crucial role of Indonesian in helping strengthen the student profile of Pancasila and national values in Karanganyar Regency Middle Schools using a sample. This research uses a qualitative descriptive method where the data results are obtained through observation and interviews as primary data and literature study to obtain secondary data. The final results of the research show that the implementation of the Pancasila Student Profile at the Junior High School level in Karanganyar Regency has been implemented and supported by various parties but still requires innovation and certain solutions to run optimally.